Preliminary Studies with Filler Organoclay Nanocomposite Making for Packaging - Yoyon Suyono (Biopropal Industri, 2012)
Clay from West Kalimantan is still used as a raw material in the ceramic industry and it doesn’t have spesific processes for the manufacture of other products. The objective of this study is to determine the effect of organoclay filler on the physical properties of tensile strength clay nanocomposite food packaging applications. The step for clay nanocomposite were produced by purification, milling, organoclay, clay nanocomposite. Clay nanocomposite were characterized by analysis cation exchange capacities (CEC), X-ray diffraction (XRD), particle size analysis (PSA), scanning electron microscopy (SEM), tensile strength test and elongation at break. The purified with hydrochloric acid can increase the value of CEC and remove of the impurities. High energy milling (HEM) technique are with a time of 2 hours gained 225.3 nm sized nanoparticles as raw material organoclay. The addition of 1% organoclay filler increases the tensile strength of nanocomposite clay, according grade 2 and is suitable for second packaging or  not directly contact to food.